E-cigarette use among Texas youth: Results from the 2014 Texas Youth Tobacco Survey. (November 2015) - Cooper, Maria; Case, Kathleen R.; Loukas, Alexandra
Abstract: Introduction: Several characteristics of electronic cigarettes (e-cigarettes), such as candy flavorings, are worrisome for attracting youth. The current cross-sectional study uses data on e-cigarette use from the 2014 Texas Youth Tobacco Survey (TYTS), a representative statewide sample of Texas middle school and high school students. This study's aims are to determine the prevalence of e-cigarette use, including rates of concurrent use with other tobacco products among Texas youth and to describe the demographic and tobacco use differences between e-cigarette users and non-users. Methods: Participants were 13, 602 6th through 12th grade students in Texas. Descriptive statistics were generated to determine the prevalence of current and lifetime e-cigarette use and to determine the prevalence of demographic characteristics across e-cigarette usage groups. Logistic regression analyses were conducted to examine differences in demographic characteristics, cigarette use in the home, and tobacco use behaviors for e-cigarette users versus non-users. Results: Almost one quarter of all middle and high school students reported lifetime e-cigarette use and 14.0% were past 30-day users of these products. Current e-cigarette users were more likely to be high school students, white and male than non-current users. Both current and lifetime e-cigarette users were also more likely than their peers to use other tobacco products, although 24.2% of current e-cigarette users had never smoked conventional cigarettes, and 7.3% had never used any other type of tobacco product besides an e-cigarette. Conclusions: Findings highlight the urgency to regulate e-cigarettes as well as to include these products in tobacco prevention programs. Highlights: We analyze current e-cigarette use in the 2014 Texas Youth Tobacco Survey. As of November 2014, Texas does not have a statewide law prohibiting e-cigarette sales to minors. We document the highest prevalence of current e-cigarette use among U.S. youth to date. We found that 24.2% of current e-cigarette users had never smoked cigarettes. In addition, 7.3% of e-cigarette users never used any other type of tobacco product.